Effect of selenium supplementation on productive performance in pigs: meta-analysis - Quisirumbay-Gaibor, Jimmy (2020)
The aim of this study was to quantify the impact of selenium supplementation in the diet on daily bodyweight gain and feed intake and feed efficiency in pigs. Twenty-seven meta-analyzes were carried out from 13 scientific articles that included a total of 9608 animals. Effect size and heterogeneity were determined under the random effects model. Selenium supplementation was found to improve daily weight gain (+5.1 g/day) and feed efficiency (+1.5 g/kg of feed). In piglets, the daily weight gain increased by 12.5 g/day (p=0.003) and 14.8 g/day (p=0.007) in the general analysis and when the source was organic, respectively. Piglet feed efficiency was improved by 11.7 (p=0.00004), 8.3 (p=0.045) and 14.9 g/kg (p=0.0002) in the general analysis, inorganic and organic source, respectively. It is concluded that dietary selenium supplementation improves the productive performance of pigs, with greater impact on piglets and when the source used was organic.